The Chinese Principal’s View of Calling in the University of Christianity——A Case Study of Lingnan University and its Principal ZHONG Rongguang - SUN, Qinghai (Journal of Research for Christianity in China (JRCC), 2025)
The View of Calling in Christian protestant requires its disciples to fulfill his job with sense of holiness and mission. This is deeply reflected in a particular group—— Chinese principal of Christianity University. ZHONG Rongguang, the first Chinese Principal of Lingnan University, boasts three great achievements in his whole life: namely, taking over the rights of education, carrying out industrial education, and raising funds aboard. These three great achievements were interwoven with how he dealt with the relationships between running school independently and raising funds aboard, religious education and industrial education , patriotism and individual faith. And all these relationships is the key for us to understand his view of calling.